Macrophage Foam Cell-Targeting Immunization Attenuates Atherosclerosis - Wang, Fazhan; Zhang, Zhi; Fang, Aiping; Jin, Quansheng; Fang, Dailong; Liu, Yongmei; Wu, Jinhui; Tan, Xiaoyue; Wei, Yuquan; Jiang, Chunling; Song, Xiangrong (Frontiers in Immunology, 2019)
Background: Macrophage foam cells (FCs) play a crucial role in the initiation and progression of atherosclerosis. Reducing the formation or inducing the removal of FCs could ameliorate atherosclerosis. The present study examined whether the whole-cell vaccination using FCs could be used as novel prevention and treatment strategies to battle atherosclerosis. Methods: ApoE−/− mice with initial or established atherosclerosis were subcutaneously immunized three times with FCs in Freund’s adjuvant. Results: Immunization with FCs resulted in an overt reduction of atherosclerotic lesion in the whole aorta and the aortic root with enhanced lesion stability. Subsequent study in mechanism showed that FCs vaccination dramatically increased CD4+ T cell and CD8+ T cell populations. Immunization with FCs significantly raised the plasma FCs-specific IgG antibodies. Of note, the FCs immune plasma could selectively recognize and bind to FC. FCs immune plasma significantly blocked the process of FCs formation, finally reduced the accumulation of FCs in plaque. Additionally, it was observed that FCs immunization down-regulated the expression level of atherosclerosis related pro-inflammatory cytokines, including IFN-γ, MCP-1 and IL-6 and enhanced the lesion stability with a significant increase in TGF-β1 level and collagen content. Conclusions: These findings demonstrate that the whole-cell vaccination using FCs significantly decreased lesion development and positively modulated lesion progression and stability by targeting FCs. The whole-cell FCs vaccine might represent a potential novel strategy for development of new antibodies and vaccines to the prevention or treatment of atherosclerosis.